FILM FICTION “TUAN X”: GESTUR APPROACH AS A PSYCHOLOGY MARK OF A MAIN FIGURE - Angelina, Ayu Mella; Abidin, Zainal; Karyadi, FX. Yatno (Capture : Jurnal Seni Media Rekam, 2018)
The film Tuan X is a fictional film with the theme of psychology. This film is very closely related to one's personal life. Films that tell about the condition of someone who is experiencing severe frustration so that his psychological was disturbed and it made him did things that are not normal. The production of Tuan X film is based on the concepts of directing, videography, editing, and sound that have been set before. From the film that was successfully created, it appears that gestures can be used to show a psychological picture of a character. The right gestures can be supported by repetition of movements so that it strengthens a character of the figure, so that the intensity of the tension / thriller of the story in reaching a climax is in accordance to the genre raised. In addition, the gesturessucceeded in becoming a signifier of the psychological reality of the character.